The institution of confiscation in civil law: Kazakhstani and international experience - Suindikov, N.M. (Bulletin of the Karaganda University “Law Series”, 2025)
The study aims to analyse the legal nature, structure and functional characteristics of the institution of the re turn of illegally acquired assets in the Republic of Kazakhstan in the context of international approaches to confiscation without conviction. The paper sets out to determine the place of the Kazakhstani mechanism among existing confiscation models and to identify the extent to which it complies with international stand ards in the field of combating illicit enrichment. The methodological basis of the study consists of compara tive legal, formal legal, historical legal and systematic methods, as well as analysis of international and na tional regulatory acts and scientific sources. This comprehensive approach has ensured the integrity and ob jectivity of the legal analysis. As a result, it has been established that the mechanism enshrined in the Law ‘On the Return of Illegally Acquired Assets to the State’ is, by its characteristics, a model of confiscation of wealth of unexplained origin. It is characterised by a limited range of subjects, the possibility of voluntary re turn of property, the application of protective measures and the redistribution of the burden of proof. The study concludes that the modern Kazakhstani model represents a nationally adapted mechanism of civil law confiscation, reflecting the transition from a punitive approach to preventive regulation of property relations. Its development contributes to strengthening public confidence in justice and improving the asset recovery system.